Enhancing Maternal Knowledge About Tuberculosis in Toddlers Through Booklet Based Health Education in Surabaya - Enung Mardiyana Hidayat; Hana Marshadita Yowanda Sari; Sri Hardi Wuryaningsih; Aida Novitasari; Mejilla Joylyn L. (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Tuberculosis causes an increase in morbidity, death, and disability in toddlers. The importance of knowledge to mothers to prevent the transmission of Tuberculosis in toddlers. This study aims to determine the Effect of the Health Education Media Booklet on Maternal Knowledge about Tuberculosis in Toddlers in the Working area of Puskesmas Perak Timur Surabaya. This research uses the Quasy Experimental method with a One Group Pre-Post Test Design approach. This research was conducted on mothers who have toddler-age children in Perak Timur and Bongkaran villages. Before the intervention, the mother's knowledge level was found to be in the sufficient category, and after the intervention, it was found that the mother's knowledge level (95.58%) was in the good category. p = 0.000 p< α = 0.05 was the outcome of the Wilcoxon Sign Rank Test analysis. The results of statistical tests show that there is an influence of health education media booklets on maternal knowledge in the working area of the Perak Timur Surabaya Health Center. Booklet media is very effective and easy to learn, so this media can be continued in the next research. Following the results of the research obtained, it was concluded that the provision of Health Education is very important, especially for areas far from the center of public health services, regular provision of Health Education should be carried out by medical officers in charge of the area.